Desain Reaktor Pengolahan Limbah Cair Laboratorium - Pabbenteng; Elisabeth Alwina (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2020)
The design of the laboratory liquid waste treatment reactor aims to treat laboratory waste so it is environmentally friendly based on physical and chemical parameters. Reducing the concentration of waste close to or in accordance with the quality standards of liquid waste and also as a waste treatment model that utilizes agricultural waste as reactor stuffing to process laboratory waste to be environmentally friendly. This research also adds economic value to cocoa skin waste, so that cocoa farmers get additional income from cocoa shells. The optimum conditions in the design of this tool occur at a flow rate of 21.94 mL / sec, the height of the adsorbent 20 cm so as to reduce the value of TSS (Total Suspended Solid) with an efficiency of 62,285% and TDS (Total Dissolve Suspended) with an efficiency of 19,415% and at optimum conditions have a pH value of 7. The method applied in this study is the filtration method and the absorption or adsorption method. The sample flow from the bottom up so that the contact between the adsorbent and the waste in the reactor is maximal because of the influence of pressure and gravity. The result of this process is the formation of fine sediments between adsorbents.